PENGARUH KEBIJAKAN HUTANG DAN PROFITABILITAS PADA NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL PEMODERASI - Pratiwi, Ni Putu Diah; Mertha, Made (E-Jurnal Akuntansi, 2017)
This study aims to determine the effect of debt policy and profitability in the company's value with dividend policy as moderating variables. This study was performed on companies listed in Indonesia Stock Exchange (BEI) in 2013-2015. Selection of the sample through purposive sampling method. There are 15 companies that meet the criteria as samples so that research data are 45 observations. The analysis technique used in this research is Multiple Linear Regression and Moderated Regression Analysis (MRA). The results of this study show that debt policy significant positive effect on the value of the company. Profitability has no effect on the value of the company. Dividend policy strengthen debt policy influence on the value of the company. The dividend policy is not able to moderate influence on the value of the company's profitability.
Keywords: debt policy, profitability, dividend policy, the company' s value